Optimizing Village Funds for Sustainable Development: A Technical Guidance Services in Tokowuta Village, Lasolo Sub-district - Upe, Ambo; Hos, Jamaluddin; Arsyad, Muhammad; Roslan, Suharty; Supiyah, Ratna (CV. Literasi Indonesia, 2024)
Synchronizing village funds with the Sustainable Development Goals (SDGs) is essential to achieve sustainable, inclusive village development and improve the welfare of village communities. Achieving these goals requires technical understanding from village government officials. Therefore, technical guidance on optimizing the utilization of village funds is crucial to ensure effective, transparent, and accountable fund management, so that it can support the achievement of the SDGs targets at the village level. This research uses lecture and case discussion methods to provide a theoretical and practical understanding of strategies to optimize the utilization of village funds in line with the SDGs. Through the combination of these two methods, it is expected that village officials can plan, implement, and supervise the use of village funds more effectively and efficiently. The results of this community service concluded that technical guidance on the optimization of village funds is essential to ensure the effective, transparent, and accountable use of village funds. Technical guidance helps village officials understand effective fund management techniques, encourages community participation, accelerates village development, and ensures funds are used as needed. Optimization of village funds supports sustainable development with a focus on good governance operations, development implementation, and community empowerment. Synchronizing village funds with the SDGs is urgent to solve village problems such as poverty and climate change, ensure inclusive and sustainable development, and improve the quality of life of rural communities.